Studi Kasus Atas Disparitas Antara Putusan Mahkamah Agung Dengan Putusan Pengadilan Niaga Mengenai Kriteria Merek Terkenal Yang Terjadi Antara Biostime Hong Kong Limited Melawan PT Bogamulia Nagadi Ditinjau Dari UU No 20 Tahun 2016 Tentang Merek Dan Ind - Galuh Ajeng Kusumoretno Nugroho; Rika Ratna Permata; Helitha Novianty Muchtar (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2023)
The urgency of the fame of a marks that is currently important makes people more aware to protect well-known marks. In the case of the "Biostime" marks dispute that occurred between H&H Hong Kong Limited and PT Bogamulia Nagadi, there were legal problems regarding the cancellation of the mark which had similarities in essence with the well-known marks. The study was to determine the disparity between the judges considerations in the Supreme Court Decision No. 781/K/Pdt.Sus-HKI/2022 and the Commercial Court Decision No. 48/Pdt.Sus-Merek/2021/PN. Niaga.Jkt.Pst is in accordance with Law Number 20 of 2016 concerning MIG; and assess the accountability of the Directorate General of Intellectual Property of the Ministry of Law and Human Rights based on Law Number 20 of 2016 concerning MIG. This research uses research methods with a normative juridical. This research stage focuses on literature studies using secondary data in the form of primary legal materials, secondary legal materials, and tertiary legal materials. In addition, field studies were conducted by conducting interviews. Based on the results of the study, 2 (two) things can be concluded. First, the disparity between the consideration of Supreme Court Justices and Commercial Court Judges is in the criteria for famous marks. Second, DJKI's responsibility is to comply with and carry out the results of court decisions and provide legal protection for marks that have been officially registered.